Prevalence of Levator Ani Defects in Urogynecological Patients - Albrich, S.; Rommens, K.; Steetskamp, J.; Weyer, V.; Hoffmann, G.; Skala, C.; Zahn, E. (Geburtshilfe und Frauenheilkunde, 2015)
Introduction: Defects of the levator ani muscle complex could represent a pathophysiological link between vaginal birth trauma and urogynecological symptoms many years later. The aim of our study was to determine the prevalence of levator ani muscle defects using 3D or 4D ultrasound and palpation in urogynecological patients. Material and Methods: Urogynecological patients were retrospectively investigated using 3D or 4D ultrasound. Clinical examination consisted of palpation and 3D or 4D imaging of the levator ani muscle. Results: A total of 319 women were included in the analysis. Mean age was 64.9 years, average parity was 2.1. Stress incontinence was present in 50.8 %, overactive bladder symptoms in 69.3 % and pelvic organ prolapse in 42.3 % of patients. A levator ani defect was found on ultrasound in 76 patients (23.8 %) and on palpation in 64 women (20.0 %). In the group of patients with pelvic organ prolapse, levator ani defects were found in 32.6 % of patients using ultrasound and in 26.7 % of patients using palpation. The odds ratio (OR) for levator ani defects in women with pelvic organ prolapse was 2.3 (95 % CI [CI: confidence interval]: 1.36–3.88], p = 0.002). Conclusion: In a cohort of urogynecological patients seen at a tertiary urogynecological unit, the prevalence of levator ani defects was significantly higher in women with pelvic organ prolapse compared to women with stress incontinence or urge symptoms.
Keywords: uterine prolapse; sonography; urinary incontinence